Sulfur concrete for haul road construction at Suncor oil sands mines - Abraha, Dawit G; Sego, David C; Biggar, Kevin W; Donahue, Robert (Canadian Geotechnical Journal, 2007)
The feasibility of constructing mine roads at oil sands mines (Fort McMurray, Alberta) using concrete prepared from bitumen extraction and upgrading by-products and mine wastes (sulfur, fly ash, coke, and tailing sand) is evaluated. An extensive laboratory test program, including unconfined compression testing, sonic velocity measurement, and split tensile and freeze–thaw durability tests, was carried out to characterize the physical and mechanical properties of different mix designs of sulfur concrete. A study of the geochemical interaction of sulfur concrete with the near-surface environment included short-term interaction of surface-exposed sulfur concrete during the construction and operational life of the haul road and long-term interaction of sulfur concrete with groundwater following its eventual burial with mine wastes in the mined-out pits. Haul road test sections were designed based on the critical strain and resilient modulus design method. Stress and strain distributions in the selected haul road cross section induced by the truck tires were calculated using finite element analysis. Required pavement layer thicknesses were then determined on the basis of the truck loads, and resilient modulus and strength of the sulfur concrete and subgrade material using the critical strain and resilient modulus design method.Key words: sulfur concrete, mine haul road design, concrete pavement.